Severity of Imunisation Adverse (KIPI) Based on Allergic History and Vaccine Stages - Taufiqur Rahman; Abdan Syakura; Nur Rahma; Cantika Iva Nugrahani (Jurnal Penelitian Pendidikan IPA, 2025)
Covid-19 prevention has also entered a new era with the availability of the Covid-19 vaccine, which has undergone clinical trials and has been mass-produced to enhance immunity. However, the administration of vaccinations has resulted in unexpected reactions known as Adverse Events Following Immunization (KIPI). This phenomenon suggests that low vaccination rates may be associated with perceived dangerous KIPI reactions, which can be attributed to doubts and misinformation about vaccines. This study used a correlation analytical research design with a retrospective method. The population of this study consisted of all individuals who had received vaccination and experienced KIPI reactions in the working area of Teja Health Center, totaling 30 people. The characteristics of the respondents, as seen from their allergic history and vaccine stages, showed a significant correlation (p = 0.027 < 0.05). The p-value for vaccine stages was 0.000, indicating a significant relationship with the severity of KIPI reactions in Covid-19 vaccine recipients. However, age and gender were not significantly associated with the severity of KIPI reactions. The severity of KIPI reactions in Covid-19 vaccine recipients has a significant correlation with the characteristics of the respondents, as seen from their allergic history and vaccine stages.